International Digestive Endoscopy Network consensus on the management of antithrombotic agents in patients undergoing gastrointestinal endoscopy - Seung Joo Kang; Chung Hyun Tae; Chang Seok Bang; Cheol Min Shin; Young-Hoon Jeong; Miyoung Choi; Joo Ha Hwang; Yutaka Saito; Philip Wai Yan Chiu; Rungsun Rerknimitr; Christopher Khor; Vu Van Khien; et al. (Korean Society of Gastrointestinal Endoscopy, 2024)
Antithrombotic agents, including antiplatelet agents and anticoagulants, are widely used in Korea because of the increasing incidence of cardiocerebrovascular disease and the aging population. The management of patients using antithrombotic agents during endoscopic procedures is an important clinical challenge. The clinical practice guidelines for this issue, developed by the Korean Society of Gastrointestinal Endoscopy, were published in 2020. However, new evidence on the use of dual antiplatelet therapy and direct anticoagulant management has emerged, and revised guidelines have been issued in the United States and Europe. Accordingly, the previous guidelines were revised. Cardiologists were part of the group that developed the guideline, and the recommendations went through a consensus-reaching process among international experts. This guideline presents 14 recommendations made based on the Grading of Recommendations, Assessment, Development, and Evaluation methodology and was reviewed by multidisciplinary experts. These guidelines provide useful information that can assist endoscopists in the management of patients receiving antithrombotic agents who require diagnostic and elective therapeutic endoscopy. It will be revised as necessary to cover changes in technology, evidence, or other aspects of clinical practice.